2020
DOI: 10.1155/2020/8895078
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Dyssynchrony Measured by Strain Echocardiography as a Marker of Proarrhythmic Remodeling and Oxidative Stress in Cardiac Surgery Patients

Abstract: Aging leads to structural and electrophysiological changes that increase the risk of postoperative atrial arrhythmias; however, noninvasive preoperative markers of atrial proarrhythmic conditions are still needed. This study is aimed at assessing whether interatrial dyssynchrony determined using two-dimensional speckle tracking echocardiography relates to proarrhythmic structural and functional remodeling. A cohort of 45 patients in sinus rhythm referred for cardiac surgery was evaluated by echocardiography an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Patients with POAF have increased RA basal superoxide release, associated with higher tissue protein level of monoamine oxidase, NADPH oxidase 2, and p22phox subunits of NADPH oxidase. Although causality is yet to be demonstrated, atrial NADPH oxidase may be a key mediator of atrial oxidative stress that leads to the development of POAF [14]. Additionally, a study demonstrated the role of exogenous nitric oxide in reducing the incidence of POAF by using nitroprusside as a nitric oxide donor [15].…”
Section: Preoperative Substrate For the Development Of Poafmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with POAF have increased RA basal superoxide release, associated with higher tissue protein level of monoamine oxidase, NADPH oxidase 2, and p22phox subunits of NADPH oxidase. Although causality is yet to be demonstrated, atrial NADPH oxidase may be a key mediator of atrial oxidative stress that leads to the development of POAF [14]. Additionally, a study demonstrated the role of exogenous nitric oxide in reducing the incidence of POAF by using nitroprusside as a nitric oxide donor [15].…”
Section: Preoperative Substrate For the Development Of Poafmentioning
confidence: 99%
“…The substrates and mechanisms mentioned above are summarized in Table 2. [14,[22][23][24][25] calcium handling…”
Section: Preoperative Substrate For the Development Of Poafmentioning
confidence: 99%
See 2 more Smart Citations
“…A good balance between ROS and RNS with antioxidants is necessary for proper physiological function. Both ROS and RNS participate in the emergence of oxidative stress [1,2]. Oxidative stress plays an important role in the development of age-related diseases including arthritis, diabetes, dementia, cancer, atherosclerosis, vascular disease, osteoporosis, and metabolic syndrome [3,4].…”
Section: Introductionmentioning
confidence: 99%